Interactions between main Central American and the U.S. stock markets with financial contagion: An application of the FIEC-FIAPGARCH-DCC model - Liu, Hsiang-Hsi (Edelweiss Applied Science and Technology, 2025)
Given the limited empirical evidence on the relationship between the main Central American stock markets (Costa Rica and Panama) and the U.S. stock market, this study aims to empirically examine volatility spillovers, long memory characteristics, asymmetries, and dynamic conditional correlation (DCC) effects among these markets. In addition, we investigate the contagion effects of major financial events across the three stock markets using a multivariate Fractionally Integrated Error Correction (FIEC) model and a Fractionally Integrated Asymmetric Power GARCH (FIAPGARCH) model within DCC framework. Structural breaks associated with the subprime mortgage and Global Financial Crisis (GFC), as well as European Debt Crisis (EDC), are explicitly incorporated into the analysis. Our findings reveal significant cross-market effects, evidence of long-term volatility dependence, and asymmetric volatility responses to positive and negative shocks. Moreover, estimating the power term parameters allows for a nuanced understanding of variance heterogeneity across markets. The observed market interactions stem not only from fundamental co-movement but also from contagion effects triggered by systemic events such as the GFC and EDC. These insights provide valuable implications for financial risk managers, regulators and international investors, offering guidance for portfolio diversification, risk assessment, and strategic asset allocation decisions in an increasingly interconnected global market environment.